In vivo CYP3A activity in palliative care patients: study protocol for a single arm prospective trial - Geist, Marcus Julian Peter; Bardenheuer, Hubert J.; Burhenne, Jürgen; Mikus, Gerd (Journal of palliative medicine, 2018)
Background: Drug interactions are a common cause for escalation of debilitating symptoms in palliative care patients. CYP3A is the most relevant CYP enzyme in humans involved in metabolism of about half of all available pharmaceuticals.Objective: To increase knowledge about the CYP3A enzyme and the impact of drug interactions on its activity to improve dosing in palliative care patients.Design: The prospective clinical trial uses a secure method of analyzing CYP3A activity in humans: Administration of a marker substance followed by the determination of its blood concentrations as well as the concentrations of its metabolite at certain points of time and corresponding metabolic clearance calculations.Setting: The ongoing trial is carried out at a palliative care unit under real-life clinical conditions.Measurements: A four-hour pharmacokinetic profile after oral administration of the marker substance (microdose of midazolam) will be obtained from each enrolled patient. Plasma concentrations of midazolam and its primary metabolite will be quantified by mass spectrometry techniques. CYP3A activity will be calculated as partial metabolic clearance from a limited sampling area under the curve. All other drugs taken by the participating patients will be considered as well as recent blood test results and the patients' diagnoses.Conclusions: This is the first prospective study dealing with drug metabolism in patients on a palliative care unit. The trial is based on reliable and established methods aiming to provide improved dosing regimens and thus optimize pharmacological therapies in this specialty.